(3GdMSGHGJ GdbhejI (B/s - (3Rjfj, YHO GdMSjfs ((3YeGf(B: s (3OGQ hecJHI GdMGeO ddfTQ hGdJhRjY(B, s, 2012)
(3eaGgje hJYGQja GdONd hGdMSGHGJ GdbhejI(B- (3MSGH GdONd Gdbhej HWQjbI GdbjeI GdeVGaI(B- (3JbOjQ GdONd Gdbhej HWQjbI GdMUU GdehRYI(B- (3JbOjQ GdONd Gdbhej HWQjbI GdEfaGb(B- (3GdMSGHGJ GdbhejI aj JhUjGJ GdCee GdeJMOIs
Keywords: (3GdMSGHGJ GdbhejIs; (3GdONds; (3GdONd Gdbhejs